Preoperative Radiotherapy in Rectal Cancer - Irwan Ramli; - Sudibio; Fitri Anugrah (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2019)
Rectal cancer is the third most common types cancer in the world and rank second as a cause of cancer related deaths in 2018. Surgical is the main modality in treatment of rectal cancer, however preoperative radiotherapy significantly reduces local recurrence risk after surgery. At present there are two different schedules of preoperative radiotherapy, short-course preoperative radiotherapy (25 Gy at 5 fractions) followed by immediate surgery and long-course chemoradiotherapy (45-50 Gy at 25-28 fractions) followed by delayed surgery. Although the purpose and local control rate of both schedules is the same, it is indicated in different conditions.